Penerapan Akuntansi Pertanggungjawaban sebagai Alat Penilaian Kinerja Pusat Biaya PT. Gudang Garam Tbk - Panji Bagus Dewanata (Universitas Nusantara PGRI Kediri, 2019)
PT. Gudang Garam is a company that produces cigarettes from Indonesia which is one of the largest cigarette factories in Indonesia. This type of research is descriptive qualitative that focuses on accountability accounting as a cost center performance appraisal tool. The methods used in this research are observation, interviews, literature study and documentation. Checking the validity of the data in this study using triangulation of sources which is done by checking the data obtained by several sources. The conclusions of this study are (1) the preparation of the budget at PT. Gudang Garam Tbk is prepared based on the work program of each responsibility center and is prepared by the finance and administration managers together with the budget department. This means that in preparing the budget, the company does not involve all managers in the company, so it is not in accordance with the proper application of the concept of accountability accounting. (2) Company management does not evaluate the budget periodically. Evaluation is only carried out at the end of each period and that is only limited to determining the difference between the budget and the realization. (3) In implementing the reward and punishment system at PT. Gudang Garam Tbk has implemented a bonus system (incentive) for managers who excel.